Surface construction using continuous trigonometric Bézier curve - Ismail, Nur Hidayah Mohammad; Misro, Md Yushalify (AIP conference proceedings, 2020)
In this paper, continuous curves using different levels of continuity are being evaluated and compared as the degree of Bézier curve increases. Unfortunately, the ordinary Bézier curve lacks flexibility in controlling the shape of the curve. Therefore, quintic trigonometric Bézier curve is introduced as an alternative to produce a flexible continuous curve. The smooth continuous curve will act as a curve generator into producing desired shapes. Additionally, by applying quintic trigonometric Bézier curve on an object, the curve generator will undergo a sweeping technique in order to form a surface.